The Application of Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) Approach to Increase the Motivation and Learning Outcomes of Students on the Material of Transport through Membranes - Seri Amalia; Safrida S; Susi Mulia Ulva (Postgraduate, University of Mataram, 2024)
Teaching at The Right Level (TaRL), is a learning approach by orienting learners to carry out learning. The purpose of this study is to design and implement learning by applying the Teaching at the Right Level (TaRL) approach and applying the Culturally Responsive Teaching (CBT) approach that connects the cultural background of learners with material content. The methods carried out in this study include the preparation stage of compiling assessments, designing, preparing modules, the implementation stage, the evaluation stage and follow-up. The results of this study indicate that the application of Teaching at the right Level (TaRL) and Culturally Responsive Teaching (CRT) approaches is very appropriate to be used in the learning process to meet the diverse ability levels of learners, material content that is associated with the culture of learners raises learners' awareness of their own cultural identity. The use of digital learning media motivates learners in learning because there is an element of novelty and in accordance with technological developments.